A historical perspective on radioisotopic tracers in metabolism and biochemistry. (March 2015) - Lappin, Graham
Radioisotopes are used routinely in the modern laboratory to trace and quantify a myriad of biochemical processes. The technique has a captivating history peppered with groundbreaking science and with more than its share of Nobel Prizes. The discovery of radioactivity at the end of the 19th century paved the way to understanding atomic structure and quickly led to the use of radioisotopes to trace the fate of molecules as they flowed through complex organic life. The 1940s saw the first radiotracer studies using homemade instrumentation and analytical techniques such as paper chromatography. This article follows the history of radioisotopic tracers from meager beginnings, through to the most recent applications. The author hopes that those researchers involved in radioisotopic tracer studies today will pause to remember the origins of the technique and those who pioneered this fascinating science.